Aldosterone Increases Early Atherosclerosis and Promotes Plaque Inflammation Through a Placental Growth Factor‐Dependent Mechanism - McGraw, Adam P. (Blackwell Publishing Ltd, 2013)
BACKGROUND: Aldosterone levels correlate with the incidence of myocardial infarction and mortality in cardiovascular patients. Aldosterone promotes atherosclerosis in animal models, but the mechanisms are poorly understood. METHODS AND RESULTS: Aldosterone was infused to achieve pathologically relevant levels that did not increase blood pressure in the atherosclerosis‐prone apolipoprotein E–knockout mouse (ApoE−/−). Aldosterone increased atherosclerosis in the aortic root 1.8±0.1‐fold after 4 weeks and in the aortic arch 3.7±0.2‐fold after 8 weeks, without significantly affecting plaque size in the abdominal aorta or traditional cardiac risk factors. Aldosterone treatment increased lipid content of plaques (2.1±0.2‐fold) and inflammatory cell content (2.2±0.3‐fold), induced early T‐cell (2.9±0.3‐fold) and monocyte (2.3±0.3‐fold) infiltration into atherosclerosis‐prone vascular regions, and enhanced systemic inflammation with increased spleen weight (1.52±0.06‐fold) and the circulating cytokine RANTES (regulated and normal T cell secreted; 1.6±0.1‐fold). To explore the mechanism, 7 genes were examined for aldosterone regulation in the ApoE−/− aorta. Further studies focused on the proinflammatory placental growth factor (PlGF), which was released from aldosterone‐treated ApoE−/− vessels. Activation of the mineralocorticoid receptor by aldosterone in human coronary artery smooth muscle cells (SMCs) caused the release of factors that promote monocyte chemotaxis, which was inhibited by blocking monocyte PlGF receptors. Furthermore, PlGF‐deficient ApoE−/− mice were resistant to early aldosterone‐induced increases in plaque burden and inflammation. CONCLUSIONS: Aldosterone increases early atherosclerosis in regions of turbulent blood flow and promotes an inflammatory plaque phenotype that is associated with rupture in humans. The mechanism may involve SMC release of soluble factors that recruit activated leukocytes to the vessel wall via PlGF signaling. These findings identify a novel mechanism and potential treatment target for aldosterone‐induced ischemia in humans.